2019
DOI: 10.1177/0954406219856383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infill pattern and infill density at varying part orientation on tensile properties of fused deposition modeling-printed poly-lactic acid part

Abstract: Fused deposition modeling is an additive manufacturing process in which successive layers of material are deposited to create a three-dimensional object. It is the most widely used additive manufacturing process because of its ability to make specimen having difficult geometrical shape. However, building end-user functional parts using fused deposition modeling proved to be a challenging task because of a wide variety of processing parameters. In the present paper, a detailed experimental study on open source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 24 publications
1
42
0
1
Order By: Relevance
“…A similar effect is observed for the infill percentage (the quantity of build material), where the mechanical strength improves with an increase in material density [ 45 , 46 ]. According to Dave et al [ 35 ], the infill percentage of 100% results in strong bond formation between each layer, thus making the structure dense and stronger. However, with a decrease in infill %, the gap between printed layers becomes broader and reduces bonding strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect is observed for the infill percentage (the quantity of build material), where the mechanical strength improves with an increase in material density [ 45 , 46 ]. According to Dave et al [ 35 ], the infill percentage of 100% results in strong bond formation between each layer, thus making the structure dense and stronger. However, with a decrease in infill %, the gap between printed layers becomes broader and reduces bonding strength.…”
Section: Resultsmentioning
confidence: 99%
“…In order to ensure the uniformity of test specimens, each specimen is printed separately by locating it in the middle of the printing bed in a flat orientation. Dave et al [ 35 ] concluded that flat orientation provides good mechanical strength to 3D printed parts through the FDM technique. PLA material is extruded at 240 °C at a speed of 130 mm/s by maintaining the heated bed surface at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The other parameters were chosen based on the scientific literature. In particular, a rectilinear infill pattern with a 0 • raster angle was chosen in order to optimize the tensile properties (especially, the rigidity); 80% infill rate and 45 mm/s printing speed were chosen as a compromise solution between better properties and higher production rate; three perimeter shells also on the basis of studies on similar systems using FDM 3D-printing [8][9][10]. The obtained 3D-printed samples and their codes are summarized in Table 2, while some representative samples are shown on Figure 4.…”
Section: Fdm Of the Biocompositesmentioning
confidence: 99%
“…Several experimental studies focused on the effects on the properties of the manufactured systems, using acrylonitrile-butadiene-styrene copolymer (ABS) [8,9] or polylactic acid (PLA) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this research limits the investigation only for hilbert curve, gyroid, archimedean chords, line, 3D honeycomb, octagram spirals, rectilinear, stars, cubic, triangle, concentric, grid, and honeycomb patterns as shown in Figure 2. Dave et al [11] explored the effect of infill density and infill pattern on tensile properties and modes of failure. Quanjin et al [12] compared five infill pattern structures, which are normal, triangle, square, hexagonal, and tetrahedral patterns, of single polylactic acid tubes and hybrid tubes on their energy-absorbing characteristics.…”
Section: Introductionmentioning
confidence: 99%